DESKRIPSI MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA BERDASARKAN JENIS KELAMIN DI SMPN 1 BUKITTINGGI - Silvia Ramadani; Aniswita Aniswita; Elydar Elydar (Universitas Pahlawan Tuanku Tambusai, 2022)
Interest in student learning is a willingness or desire in students to learn something. In this study, the researchers discussed the interest in learning mathematics in students based on gender in class 8 D of SMPN 1 Bukittinggi in the 2022 academic year. This research has the objective of describing the interest in learning mathematics in male and female students in class 8 D SMPN 1 Bukittinggi . The method in this research is descriptive qualitative. Where the subjects in this study were 8 D grade students, totaling 25 people and the homeroom teacher for class 8 D SMPN 1 Bukittinggi. In collecting data, researchers used a questionnaire. The results of this study are: student questionnaire data as a whole average percentage of 59%. So the conclusion is that most of the 8th grade students have an interest in learning mathematics. Meanwhile, based on gender, the results showed that the interest in learning mathematics for male students was higher than that for female students (60% > 59%). Keywords: Interest in learning, Mathematics, Gender.